The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s10096-011-1379-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human clinical isolates of Dietzia species previously misidentified as Rhodococcus equi

Abstract: In this study, 16 human clinical isolates of Dietzia species previously misidentified as Rhodococcus equi were evaluated using phenotypic methods, including traditional and commercial (API Coryne) biochemical tests, antimicrobial susceptibility testing, and 16S rRNA gene and gyrB gene sequencing. Positive results for both the hydrolysis of adenine and Christie-Atkins-Munch-Petersen (CAMP) reaction allowed for differentiation between the Dietzia isolates and the type strain of Rhodococcus equi; however, traditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
17
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
1
17
1
1
Order By: Relevance
“…This aerobic, catalase-positive, and oxidase-negative bacterium was found to grow at temperatures in the range of 22 to 45°C, forming smooth and yellow-pigmented colonies. In addition, Yassin and colleagues found that the type strain, DSM (11). Urea hydrolysis was also proven to be negative in commercial identification kits used in our study.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…This aerobic, catalase-positive, and oxidase-negative bacterium was found to grow at temperatures in the range of 22 to 45°C, forming smooth and yellow-pigmented colonies. In addition, Yassin and colleagues found that the type strain, DSM (11). Urea hydrolysis was also proven to be negative in commercial identification kits used in our study.…”
supporting
confidence: 62%
“…The colonial difference is best seen after 3 days of incubation, as all other Dietzia spp. have been shown to form at least slightly mucoid colonies in this time period (11). Furthermore, in clinical samples, Dietzia spp.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…Dietzia sp. are only rarely reported as pathogens although they may often be misidentified, notably as rhodococci [2,8].…”
Section: Introductionmentioning
confidence: 99%